2017
DOI: 10.1186/s12983-017-0193-1
|View full text |Cite
|
Sign up to set email alerts
|

Perception of emotional valence in horse whinnies

Abstract: BackgroundNon-human animals often produce different types of vocalisations in negative and positive contexts (i.e. different valence), similar to humans, in which crying is associated with negative emotions and laughter is associated with positive ones. However, some types of vocalisations (e.g. contact calls, human speech) can be produced in both negative and positive contexts, and changes in valence are only accompanied by slight structural differences. Although such acoustically graded signals associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 66 publications
(115 reference statements)
2
30
1
Order By: Relevance
“…This is what we attempted in horses, by playing back, as described in the Discrimination of emotional valence section, whinnies produced during social reunion ( positive) and separation (negative). However, we did not find clear evidence for state matching between emitters and receivers, because horses did not display more behaviours indicating negative emotions (head high [8]) during playbacks of negative whinnies, nor more behaviours suggesting positive emotions (chewing motion [8]) during playbacks of positive whinnies [29]. Similar tests conducted in other species would thus be useful to show if contagion of valence can indeed occur within a given vocalization type and thus result from the information about emotional valence conveyed in these calls, more than their function.…”
Section: (Ii) Contagion Of Emotional Valencecontrasting
confidence: 72%
See 1 more Smart Citation
“…This is what we attempted in horses, by playing back, as described in the Discrimination of emotional valence section, whinnies produced during social reunion ( positive) and separation (negative). However, we did not find clear evidence for state matching between emitters and receivers, because horses did not display more behaviours indicating negative emotions (head high [8]) during playbacks of negative whinnies, nor more behaviours suggesting positive emotions (chewing motion [8]) during playbacks of positive whinnies [29]. Similar tests conducted in other species would thus be useful to show if contagion of valence can indeed occur within a given vocalization type and thus result from the information about emotional valence conveyed in these calls, more than their function.…”
Section: (Ii) Contagion Of Emotional Valencecontrasting
confidence: 72%
“…Evidence for discrimination of vocal expression of emotional valence is sparse. My colleagues and I have tested the ability of horses (Equus caballus) to differentiate between positive and negative whinnies by directly playing back these two whinny variants separately (without habituation) [29]. This allowed us to investigate, simultaneously, discrimination and contagion of valence (see the Contagion of emotional valence section for the results regarding contagion).…”
Section: (B) Discrimination Of Emotional Valencementioning
confidence: 99%
“…Horses' acoustic communication has not been thoroughly investigated, and although whinnies are known to encode both social [123] and emotional information [142], information carried by non-vocal communication (snore, snort, blows) are less clear. Because descriptions are imprecise, snorts and snores have been confused for a long time, both were considered as indicative of high emotional states [143,144].…”
Section: Acoustic Signalsmentioning
confidence: 99%
“…A signal performed by an individual could induce in the receiver both the same arousal level (i.e., contagion of emotional arousal) and the valence (i.e., contagion of emotional valence). Briefer et al [106] evaluated if horses are able to decode the emotional valence and arousal of whinnies performed by familiar or unfamiliar conspecifics and whether any form of emotional contagion occurs. Results showed no clear evidence of contagion of emotional valence; nonetheless, authors demonstrated that horses reacted differently to separation and reunion whinnies when they are produced by familiar conspecifics, but no differences were found when unfamiliar individuals performed them, thus advocating the occurrence of emotional arousal transfer.…”
Section: Horses' Perception and Communication Of Emotionsmentioning
confidence: 99%